The clinical efficacy of external application of mirabilite and rhubarb combined with intrathoracic chemotherapy in treating malignant pleural effusion: A prospective, randomized, controlled clinical trial. Issue 7 (19th February 2021) - Zhang, Huachun; Jiang, Mengyuan; Gao, Lirong; Lin, Zhen
Abstract: Background: Malignant pleural effusion (MPE) is one of the commonest causes of an exudative pleural effusion. Breathlessness, dyspnea and other symptoms often seriously distress and affect the quality of life. The external application of mirabilite and rhubarb (EAMR) combined with intrathoracic infusion of cisplatin, as an alternative treatment for MPE, is popular in China. The study aims to assess its effectiveness and safety combined with intrathoracic chemotherapy. Methods: This study is a prospective, randomized controlled clinical trial. Patient visits were performed at baseline and days 14 and 28 after treatment. Clinical outcomes were measured after chest drain placement using the criterion of efficacy refer to WHO standard, and QLQ-C30 questionnaire. Results: Database records of patients treated in our institution for MPE between October, 2016 and March, 2019. The study included 84 eligible patients. They were categorized with a randomization schedule into treatment group (N = 42) and control group (N = 42). There is statistical significance in the comparison of the total effective rate between these 2 groups (66.67% vs 54.76%, P < .05). Furthermore, there is statistical significance in the comparison of items of Physical (1.95 ± 0.50 vs 2.19 ± 0.58%, P < .05), Pain (1.98 ± 0.42 vs 2.07 ± 0.32, P < .05), and Global Health (1.23 ± 0.64 vs 1.13 ± 0.23%, P < .05) between these 2 groups. None of the patients had adverse reactions such as skin allergy and chest tightness. Conclusions: The total effective rate of treatment group using extra external application of mirabilite rhubarb powder is significantly higher than that of control group. The improvement of patients' clinical symptoms is greater in treatment group and no adverse reactions is found. Therefore, external application of mirabilite and rhubarb combined with intrathoracic infusion of cisplatin is an effective method for the treatment of MPE, which is worth popularizing.